2018
DOI: 10.1016/j.jjcc.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiplatelet therapy after coronary stent implantation: Individualizing the optimal duration

Abstract: Dual antiplatelet therapy (DAPT) with a P2Y receptor antagonist in addition to aspirin is the antiplatelet treatment of choice in patients undergoing percutaneous coronary intervention. Despite DAPT being one of the most widely investigated treatment strategies in the cardiology field, its optimal duration after coronary stenting remains controversial. The balance between the possible benefit of preventing a thrombotic event and the risk of suffering a bleeding complication due to maintenance of therapy is of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…This strategy is empirical and based, first and foremost, on current recommendations for patients undergoing percutaneous coronary interventions. 25 Further, anatomopathological analyses have suggested that neointimal tissue invasion and full endothelialisation of the valve stent frame occur approximately 3 months after the procedure, with a decrease in thromboembolic events thereafter, which might support this antithrombotic strategy. 36 Recent evidence, however, has questioned the usefulness and safety of DAPT over SAPT with aspirin.…”
Section: Guidelines Recommendationsmentioning
confidence: 94%
See 1 more Smart Citation
“…This strategy is empirical and based, first and foremost, on current recommendations for patients undergoing percutaneous coronary interventions. 25 Further, anatomopathological analyses have suggested that neointimal tissue invasion and full endothelialisation of the valve stent frame occur approximately 3 months after the procedure, with a decrease in thromboembolic events thereafter, which might support this antithrombotic strategy. 36 Recent evidence, however, has questioned the usefulness and safety of DAPT over SAPT with aspirin.…”
Section: Guidelines Recommendationsmentioning
confidence: 94%
“…Regardless, a period of dual antiplatelet therapy (DAPT) after coronary revascularisation is mandatory, which has also evident implications in the decision-making process of selecting the antithrombotic treatment regimen after TAVI. 25,26 The spectrum of bioprosthetic leaflet thrombosis comprises subclinical imaging findings, such as early reduced leaflet motion and hypoattenuated leaflet thickening, to clinically apparent valve thrombosis with elevated gradients and clinical manifestations (i.e. heart failure, valve dysfunction and stroke or systemic embolisms).…”
mentioning
confidence: 99%
“…Investigators of the SECURITY RCT report a 12-month cumulative incidence of BARC 3 or 5 (i.e., CABG related bleeding excluded) major bleeding after DAPT with clopidogrel of 1.1% [18]. Other explanatory RCTs report a 12-month cumulative incidence in the range 0.5-1.5%, with differing bleeding definitions [2,17], while the 12-month cumulative incidence of Thrombolysis in Myocardial Infarction (TIMI) major bleeding was around 0.7% (1.3% if minor bleeding is included) in the derivation cohort for the PRECISE-DAPT score; bleeding events in the first seven days were excluded [3]. In the DAPT RCT, 2.7% of patients were excluded before randomization, due to a GUSTO major bleeding during the initial 12 months [19].…”
Section: Incidence Of Major Bleedingmentioning
confidence: 99%
“…Dual antiplatelet therapy (DAPT) is mandatory after percutaneous coronary intervention (PCI) with stent implantation in order to prevent ischemic events [1]. The optimal duration of DAPT, however, is debated [2]. The risk of ischemic events must be balanced against the risk of major bleeding imposed by the antithrombotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic oral anticoagulation (OAC) is superior to antiplatelet therapy (whether monotherapy or dual therapy) when it comes to the prevalence of thromboembolic complications (stroke and systemic embolism) of AF, 6,7 while the dual antiplatelet therapy (DAPT) with acetylsalicylic acid (ASA) and a P2Y 12 receptor inhibitor (P2YI 12 ) is the antithrombotic therapy of choice to prevent atherothrombotic ischemic events (myocardial infarction and stent thrombosis) in patients who undergo PCI (in the context, or not, of an ACS). 8,9 When both situations occur picking the antithrombotic therapy becomes a clinical issue because it is well-known that the easiest choice, that is, the use of triple antithrombotic therapy (TAT plus OAC and dual antiplatelet therapy) increases the risk of major hemorrhages at least 2 to 3-fold compared to any other antithrombotic regimens, whether dual antiplatelet therapy or dual antithrombotic therapy (DAT plus OAC and one antiplatelet drug). 10,12 Therefore, controversy arises on whether or not using TAT due to the increase of hemorrhagic complications and the possible increase of ischemic events when using less aggressive therapies like DAT.…”
Section: Antithrombotic Therapy With Vitamin K Antagonists: Dual or Tmentioning
confidence: 99%